Distributed output feedback control of decomposable LPV systems with delay and switching topology: application to consensus problem in multi-agent systems. Issue 9 (2nd September 2021) - Zakwan, Muhammad; Ahmed, Saeed
Abstract : This paper presents distributed output feedback control of a class of distributed linear parameter varying systems with switching topology and parameter varying time delay. To formulate the synthesis conditions for the distributed controller in terms of LMIs, the delay dependent bounded-real lemma based on parameter-dependent Lyapunov–Krasovskii functionals is used. The efficacy of the result is illustrated by applying it to two real-world examples pertaining to the consensus problem of multi-agent systems.